KONSTRUKSI TAHLIL KELILING SELAMA BULAN RUWAH - Idris, Muhammad Anwar (UIN Sunan Kalijaga Yogyakarta, 2020)
AbstractJavanese society is known for its people who hold tightly to traditions from their ancestors, one of which is tahlilan. Tahlilan is an inseparable part in the midst of the majority of Javanese people. As with the tradition of tahlilan carried out by the people of Belor Village, Ngaringan District, Grobogan Regency, Central Java, it is a unique activity, because the implementation of tahlil is carried out alternately in each house during the intricate month. This study uses a living hadith study approach. The results of this study show that the traveling tahlil tradition is a tradition inherited from their ancestors, the implementation time is for 30 days in the month of ruwah, usually more until the middle of the month of Ramadan due to the enthusiasm of the people who want their homes to hold this tradition. The motives and goals of the perpetrators of this tradition are to send spirits or pray for families who have died through tahlil. The majority of people are not satisfied if they do not carry out this tradition and there is something missing in their life. In terms of the benefits of this activity, there are many, including strengthening the relationship between Muslims, competing to give alms and others.Keyword: Tradition, Tahlilan, Ruwah, Living HadisAbstrakMasyarakat Jawa dikenal dengan masyarakat yang memegang erat tradisi-tradisi peninggalan nenek moyang, salah satunya adalah tahlilan. Tahlilan merupakan bagian yang tidak dapat dipisahkan di tengah-tangah mayoritas masyarakat Jawa. Seperti halnya tradisi tahlilan yang dilakukan oleh masyarakat Desa Belor Kecamatan Ngaringan Kabupaten Grobogan Jawa Tengah menjadi kegiatan yang unik, karena pelaksanaan tahlil dilakukan keliling bergantian setiap rumah selama bulan ruwah. Penelitian ini menggunakan pendekatan kajian living hadis. Hasil dari penelitian ini bahwasannya tradisi tahlil keliling ini merupakan tradisi tinggalan nenek moyang mereka, waktu pelaksanaanya ialah selama 30 hari di bulan ruwah, bahkan biasanya lebih sampai pertengahan bulan ramadhan dikarenakan antusianya masyarakat yang ingin rumahnya mengadakan tradisi ini. Adapun motif dan tujuan para pelaku tradisi ini adalah ingin mengirim arwah atau mendoakan keluarga yang telah meninggal dunia melalui tahlil. Mayoritas masyarakat merasa belum puas jika tidak mengadakan tradisi ini serta ada yang kurang dalam hidupnya. Dari sisi manfaat kegiatan ini sangatlah banyak diantaranya mempererat tali silaturahmi sesama umat Islam, berlomba-lomba ingin mengulurkan sedekah dan lain-lain.Kata kunci : Tradisi, Tahlilan, Ruwah, Living Hadis